Les lisières du Parc national de forêts comme témoin d’une mémoire environnementale - Agnès Guerin; Gabriel Barrès; Valentin Brochet; Ulysse Chabroux; Capucine Garnier Muller; Amandine Reist; Emma Weingand; Gaëlle Ronsin (Carnets de Géographes)
French national parks are now trying to protect landscapes based on social and natural interactions. Edges are an example of landscape entities that combine multiple dimensions. They form an “environmental memory of the forest”, revealing the very diverse practices and uses of the same rural space. Today, forest edges are also a key issue in ecological continuity policies and concerns about cohabitation. Based on the case of the Parc national de forêts, created in 2019, a student workshop questions the social ecology of agroforestry edges for those involved in nature protection. We were inspired by emotional geographies tools. Firstly, the semantics surrounding edges is about a vocabulary of aestheticism that reveals concerns and properties specific to these places. Secondly, the edge is paradoxically a remarkable space for some actors, but completely non-existent and invisible for others. Finally, these places or non-places dynamically trace the environmental memories of forests and their uses in these territories.